A remanufactured magnet using waste NdFeB magnets and its preparation process

By mixing waste neodymium iron boron magnets with nanogallium nitride and nano aluminum carbide, sintering and heat treatment, high-performance remanufactured magnets are prepared, which solves the problems of low utilization rate and reduced magnetic properties of waste magnets, and achieves high efficiency Magnet remanufacturing and environmentally friendly magnet preparation.

CN117153514BActive Publication Date: 2024-12-13NINGBO HELI MAGNET TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202311348231.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-10-18
Publication Date
2024-12-13
Estimated Expiration
2043-10-18

AI Technical Summary

Technical Problem

In the prior art, the utilization rate of new NdFeB magnets made of waste NdFeB magnets is not high, and the magnetic performance will be greatly reduced when the addition ratio is too high, affecting environmental protection.

Method used

The mixed preparation method of waste neodymium iron boron magnets, nanogallium nitride and nano aluminum carbide is used to prepare remanufactured magnets with high magnetic properties and corrosion resistance through preliminary crushing, preparation of magnetic powder, mixing, molding, sintering and heat treatment.

Benefits of technology

The utilization rate of waste neodymium iron boron magnets and the corrosion resistance of remanufactured magnets are improved, while maintaining high magnetic properties, solving the problem of degradation of magnet performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004499375750000051
    Figure BDA0004499375750000051
  • Figure BDA0004499375750000061
    Figure BDA0004499375750000061
  • Figure BDA0004499375750000062
    Figure BDA0004499375750000062
Patent Text Reader

Abstract

The present application relates to the field of NdFeB magnets, and specifically to a magnet remanufactured using waste NdFeB magnets and its preparation process. A preparation method for remanufactured magnets using waste NdFeB magnets, comprising: preliminary crushing and analysis, preparation of magnetic powder, mixing and sintering and tempering, wherein magnetic powder is prepared using waste NdFeB magnets, and then nano-gallium nitride and nano-aluminum carbide are added to the magnetic powder and mixed evenly to obtain a mixed powder, which is then sintered at high temperature and heat treated. In the present application, nano-gallium nitride gradually decomposes during sintering, increases the liquid phase content, promotes the doping of nano-aluminum carbide into the grain boundary, and improves the magnetic properties of the remanufactured magnet; and nano-aluminum carbide can enhance the chemical stability of the neodymium-rich phase, thereby further improving the corrosion resistance of the remanufactured magnet; compared with the prior art, the present application effectively improves the utilization rate of waste NdFeB magnets on the basis of maintaining the magnetic properties of the remanufactured magnet, and improves the corrosion resistance of the remanufactured magnet.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of NdFeB magnets, and in particular to a method for remanufacturing magnets using waste NdFeB magnets and a preparation process thereof. Background Art

[0002] NdFeB magnets are the most cost-effective commercial magnetic materials so far due to their high coercive force and high magnetic energy product. They are widely used in many fields related to people's livelihood, such as home appliances, transportation, and medical care. With the rapid development of the NdFeB permanent magnet material industry in recent years, rare earth resources have been consumed in large quantities. On the other hand, in the production and processing of NdFeB magnet products, from the initial raw materials to the final finished products, each process inevitably produces scrap materials. Coupled with the scrapping of a large number of finished products such as NdFeB motors and electronic products, the amount of scrapped NdFeB magnets that can be used each year is very huge.

[0003] There are currently two main ways to recycle waste NdFeB magnets. One is to use chemical reagents to extract and separate elements. This method requires a large amount of chemical reagents and is not conducive to environmental protection. The other is to mix waste NdFeB magnets with NdFeB magnet raw materials to prepare new NdFeB magnets. However, in this method, the addition ratio of waste NdFeB magnets needs to be less than 40%, otherwise it is easy to cause a significant decrease in the magnetic properties of the new NdFeB magnets. This method is not conducive to the large-scale utilization of waste NdFeB magnets. Summary of the invention

[0004] In order to solve the problem of low utilization rate of existing waste NdFeB magnets in making new NdFeB magnets, the present application provides a remanufactured magnet using waste NdFeB magnets and a preparation process thereof. The proportion of waste NdFeB magnets added in the remanufactured magnet exceeds 95%, and it can also maintain high magnetic properties and has excellent corrosion resistance.

[0005] In a first aspect, the present application provides a method for preparing a remanufactured magnet using waste NdFeB magnets, using the following technical solution:

[0006] A method for preparing a remanufactured magnet using waste NdFeB magnets comprises the following steps:

[0007] (1) Preliminary crushing and analysis: The recycled waste NdFeB magnets are degreased, derusted and impurity-free, and then mechanically crushed to obtain a coarse waste powder, and then the content of each component in the coarse waste powder is analyzed;

[0008] (2) preparing magnetic powder: hydrogen-crushing the waste coarse powder, and then jet milling the waste coarse powder to obtain magnetic powder;

[0009] (3) Mixing: adding nano-gallium nitride and nano-aluminum carbide to the magnetic powder, mixing them evenly to obtain a mixed powder, and placing the mixed powder under nitrogen protection for compression molding to obtain a pressed embryo;

[0010] (4) Sintering and tempering: The pressed green body is subjected to high temperature sintering, and then subjected to primary tempering and secondary tempering heat treatment to obtain a remanufactured magnet using waste NdFeB magnets.

[0011] By adopting the above technical solution, magnetic powder prepared from waste NdFeB magnets, nano-gallium nitride and nano-aluminum carbide are mixed to form a pressed embryo. During high-temperature sintering and heat treatment, nano-gallium nitride can fill the pores and defects of the remanufactured magnets on the one hand, and on the other hand, nano-gallium nitride can improve the grain size and promote the grain boundaries to become straight and complete, thereby improving the magnetic properties of the remanufactured magnets.

[0012] The neodymium-rich phase includes a small amount of intergranular neodymium-rich phase around the main phase grains and a large part of the banded neodymium-rich phase. During high-temperature sintering and heat treatment, nano-aluminum carbide can gradually distribute the intergranular neodymium-rich phase evenly through grain boundary doping, and the main phase grains have a good magnetic isolation effect, thereby improving the coercive force of the remanufactured magnet. The addition of nano-aluminum carbide will improve the orientation of the magnet, thereby improving the remanufactured magnet's remanufactured magnet and the magnet's magnetic energy product;

[0013] Nano-gallium nitride gradually decomposes during sintering, increasing the liquid phase ratio and promoting the continuous doping of nano-aluminum carbide into grain boundaries as the liquid phase flows; the nitrogen element produced by the decomposition of nano-gallium nitride combines with the oxygen element in the remanufactured magnet and is discharged, thereby improving the corrosion resistance of the remanufactured magnet; nano-aluminum carbide, as a ceramic phase particle with high hardness and high chemical stability, can enhance the chemical stability of the neodymium-rich phase and reduce the potential difference between it and the main phase, thereby further improving the corrosion resistance of the remanufactured magnet; compared with the prior art, the present application effectively improves the utilization rate of waste NdFeB magnets while maintaining the magnetic properties of the remanufactured magnet, and improves the corrosion resistance of the remanufactured magnet.

[0014] Preferably, the mass ratio of the magnetic powder to the nano-aluminum carbide is 100:(0.25-1.5).

[0015] By adopting the above technical scheme, if the content of nano-aluminum carbide is low, it is difficult to make the intergranular neodymium-rich phase evenly distributed, thereby reducing the coercive force of the remanufactured magnet, and the improvement of the magnet orientation degree by nano-aluminum carbide is small, and the improvement of the remanufactured magnet and the magnetic energy product of the magnet is small; and the enhancement of the chemical stability of the neodymium-rich phase by nano-aluminum carbide is very small, and it is difficult to enhance the corrosion resistance of the remanufactured magnet; if the content of nano-aluminum carbide is high, the content of the banded neodymium-rich phase is increased, resulting in a decrease in the content of the intergranular neodymium-rich phase, thereby weakening the demagnetizing coupling effect and reducing the coercive force of the remanufactured magnet, and nano-aluminum carbide is a non-magnetic phase, which reduces the remanufactured magnet and the magnetic energy product of the magnet; and too much nano-aluminum carbide makes the neodymium-rich phase unevenly distributed and increases its content, providing an atomic diffusion channel for the corrosion reaction of the neodymium-rich phase, and the corrosion resistance of the magnet deteriorates; for this reason, the applicant finally determined that the mass ratio of magnetic powder to nano-aluminum carbide in this application is appropriate to be the above after a lot of research and experimental verification.

[0016] Preferably, the average particle size of the aluminum carbide is 30-50 nm.

[0017] By adopting the above technical scheme, if the particle size of nano-aluminum carbide is small, it is easy to flow into the intergranular neodymium-rich phase with the liquid band-shaped neodymium-rich phase, thereby squeezing the intergranular neodymium-rich phase into the band-shaped neodymium-rich phase, reducing the demagnetizing coupling effect of the main phase grains. At the same time, the content of the band-shaped neodymium-rich phase increases, promoting grain growth and reducing coercive force; if the particle size of nano-aluminum carbide is large, the fluidity of the intergranular neodymium-rich phase is reduced, resulting in uneven distribution of the intergranular neodymium-rich phase between the grains, reducing the demagnetizing coupling effect and reducing the coercive force; for this reason, the applicant finally determined that the average particle size of aluminum carbide in this application is preferably as above after a lot of research and experimental verification.

[0018] Preferably, the mass ratio of the magnetic powder to the nano-gallium nitride is 100:(0.25-1.5).

[0019] If the content of nano-gallium nitride is too low, it is difficult to promote uniform grain size, and it is also difficult for nano-aluminum carbide to be incorporated into grain boundaries, thereby reducing the magnetic properties of the remanufactured magnet; if the content of nano-gallium nitride is too high, Ga atoms will continuously replace Fe atoms after the decomposition of nano-gallium nitride, and the B-rich phase in the liquid phase is limited. The replaced Fe atoms can only form Nd-Fe or other compounds, thereby destroying the Nd-Fe-B phase, forming more and more irregular phases, and the grain size and distribution of the magnet are becoming more and more uneven, reducing the magnetic properties; for this reason, the applicant finally determined after a lot of research and experimental verification that the mass ratio of magnetic powder to nano-gallium nitride in this application is preferably as mentioned above.

[0020] Preferably, the average particle size of the nano-gallium nitride is 10-30 nm.

[0021] By adopting the above technical solution, if the average particle size of nano-gallium nitride is large, it will not be fully decomposed during high-temperature sintering, and the liquid phase will increase too little to promote the entry of nano-aluminum carbide into the grain boundaries, thereby reducing the magnetic properties of the remanufactured magnet; if the average particle size of nano-gallium nitride is low, it will be fully decomposed during high-temperature sintering, and for production cost considerations, there is no need for nano-gallium nitride with a finer particle size; for this reason, the applicant finally determined that the average particle size of nano-gallium nitride in this application is preferably the above after a lot of research and experimental verification.

[0022] Preferably, in step (4), the sintering temperature is 1090-1120° C., and the sintering time is 4-6 hours.

[0023] By adopting the above technical solution, when the sintering temperature is too high, the nano-gallium nitride has been fully decomposed and there is no need to continue to increase the sintering temperature; when the sintering temperature is too low, the decomposition rate of the nano-gallium nitride is slow, and it is difficult to fully promote the flow of nano-aluminum carbide into the intergranular space; for this reason, the applicant finally determined that the sintering temperature in this application is appropriate after a lot of research and experimental verification.

[0024] Preferably, in the step (4), the pressed green body is kept at 850-900°C for 2-4 hours for primary tempering, and then the pressed green body is cooled to a temperature less than 100°C using argon.

[0025] By adopting the above technical scheme, when the temperature of the first-stage tempering is too high, it has fully promoted the reduction of the inhomogeneous phase in the main phase grains, promoted the nano-aluminum carbide to enter the intergranular phase, and also promoted the decomposed Ga atoms to replace Fe atoms, without further increasing the first-stage tempering temperature; when the temperature of the first-stage tempering is too low, the reduction amount of the inhomogeneous phase in the main phase grains may be too low, hindering the nano-aluminum carbide from continuing to diffuse into the grain boundary phase; for this reason, the applicant finally determined that the first-stage tempering temperature and tempering time in this application are appropriate to be as above after a lot of research and experimental verification.

[0026] Preferably, the compact is kept at 600-640° C. for 4-6 hours for secondary tempering, and then cooled to room temperature using argon.

[0027] By adopting the above technical scheme, if the secondary tempering temperature is too high, it will promote the growth of the main phase grains and reduce the coercive force; if the secondary tempering temperature is too low, the rare earth-rich phase is easy to agglomerate at the triple grain boundary, which is easy to lead to a decrease in coercive force; for this reason, the applicant finally determined that the secondary tempering temperature and tempering time in this application are appropriate to be as above after a lot of research and experimental verification.

[0028] In a second aspect, the present application provides a remanufactured magnet using waste NdFeB magnets, using the following technical solution:

[0029] The remanufactured magnet using waste NdFeB magnets prepared by any of the above preparation methods has the same advantages as the above preparation methods over the prior art, which will not be described in detail here.

[0030] In summary, this application has the following beneficial effects:

[0031] 1. The present application adopts a mixture of magnetic powder prepared from waste NdFeB magnets, nano-gallium nitride and nano-aluminum carbide. After high-temperature sintering and heat treatment, the nano-gallium nitride first promotes the straightness and integrity of the grain boundaries, thereby improving the magnetic properties of the remanufactured magnets; then it gradually decomposes during sintering, increases the liquid phase content, promotes the doping of nano-aluminum carbide into the grain boundaries, and improves the magnetic properties of the remanufactured magnets; and nano-aluminum carbide can enhance the chemical stability of the neodymium-rich phase, thereby further improving the corrosion resistance of the remanufactured magnets; compared with the prior art, the present application effectively improves the utilization rate of waste NdFeB magnets while maintaining the magnetic properties of the remanufactured magnets, and improves the corrosion resistance of the remanufactured magnets. DETAILED DESCRIPTION

[0032] The remanufactured magnet of the present application comprises waste NdFeB magnets, nano-gallium nitride and nano-aluminum carbide.

[0033] The nano-gallium nitride is a commercially available product with a CAS number of 25617-97-4 and a purity of ≥99.99%; the nano-aluminum carbide is a commercially available product with a CAS number of 1299-86-1 and a purity of ≥99.99%.

[0034] Scrap NdFeB magnets are waste materials generated in the production of NdFeB, as well as recycled scrapped NdFeB motors, electronic products, etc.

[0035] The elemental composition of waste NdFeB magnets was measured using inductively coupled plasma optical emission spectrometry.

[0036] The contents of each component in the waste NdFeB magnets are: Pr-Nd 21.3%, Ce 9%, Cu0.15%, Co 0.3%, Ti0.15%, Ga 0.15%, Al0.3%, Gd 1.3%, B 0.92%, and the rest are Fe and unavoidable impurities.

[0037] The present application is further described in detail below in conjunction with specific embodiments and comparative examples.

[0038] Example 1

[0039] The preparation method of the remanufactured magnet comprises the following steps:

[0040] (1) Preliminary crushing and analysis: The recycled waste NdFeB magnets are degreased, derusted, and impurity-free, and then mechanically crushed to obtain a coarse waste powder, and then the content of each component in the coarse waste powder is analyzed;

[0041] (2) Preparation of magnetic powder: hydrogen crushing of the waste coarse powder, followed by jet milling to obtain magnetic powder;

[0042] (3) Mixing: adding 1 g of nano-gallium nitride and 1 g of nano-aluminum carbide to 100 g of magnetic powder, mixing them evenly to obtain a mixed powder, and then pressing the mixed powder under nitrogen protection to obtain a green compact;

[0043] (4) Sintering and tempering: Place the pressed green sheet in step (2) into a vacuum sintering furnace, evacuate to a vacuum degree of ≤1Pa, heat to 1120°C for sintering, keep the temperature for 5 hours after sintering, cool to 900°C for 3 hours, then fill with argon and cool to room temperature, then heat to 620°C for 5 hours, fill with argon and cool to room temperature, and finally obtain a remanufactured magnet.

[0044] Embodiment 2-5

[0045] In Example 2-5, based on the preparation method of Example 1, the weight ratio of the magnetic powder and the nano-aluminum carbide was adjusted. The adjustment details are shown in Table 1 below.

[0046] Comparative Example 1-2

[0047] Comparative Example 1-2 is based on the preparation method of Example 1, and the weight ratio of magnetic powder and nano-aluminum carbide is adjusted. The adjustment details are shown in Table 1 below.

[0048] Comparative Example 3

[0049] Comparative Example 3 is a remanufactured magnet prepared based on the preparation method of Example 1, using only 102g of magnetic powder.

[0050] Comparative Example 4

[0051] Comparative Example 4: Based on the preparation method of Example 1, remanufactured magnets were made by weighing the raw materials of each element whose element content was tested in the waste NdFeB magnets.

[0052] Performance testing

[0053] 1. Magnetic property detection

[0054] The remanufactured magnets provided in Examples 1-5 and Comparative Examples 1-4 of the present application were tested for magnetic properties according to GB / T 3217-2013 “Magnetic Test Methods for Permanent Magnet (Hard Magnetic) Materials”. The test results are shown in Table 2.

[0055] 2. Corrosion resistance

[0056] The remanufactured magnets provided in Examples 1-5 and Comparative Examples 1-4 of the present application were tested for weight loss according to GB / T 40792-2021 “Test method for weight loss of sintered NdFeB permanent magnets”. The test results are shown in Table 2.

[0057] Table 1 Weight ratio of magnetic powder and nano-aluminum carbide in Examples 1-5 and Comparative Examples 1-2

[0058] Magnetic powder / g Nano-aluminum carbide / g Example 1 100 1 Example 2 100 0.4 Example 3 100 0.8 Example 4 100 1.2 Example 5 100 1.5 Comparative Example 1 100 0.3 Comparative Example 2 100 1.6

[0059] Table 2 Performance test data of Examples 1-5 and Comparative Examples 1-4

[0060]

[0061]

[0062] Referring to Table 2, by comparing Examples 1-5 and Comparative Examples 1-4, it can be seen that as the content of nano-aluminum carbide continues to increase, the magnetic properties and corrosion resistance of the remanufactured magnet show a trend of first increasing and then decreasing. This may be because within a certain range, nano-aluminum carbide makes the intergranular neodymium-rich phase gradually evenly distributed, and there is a good magnetic isolation effect between the main phase grains, thereby improving the coercive force of the remanufactured magnet, and the addition of nano-aluminum carbide will improve the orientation of the magnet, thereby improving the remanufactured magnet and the magnetic energy product of the magnet; and nano-aluminum carbide is a ceramic phase particle with high hardness and high chemical stability, which can enhance the chemical stability of the neodymium-rich phase, reduce the potential difference between it and the main phase, and improve the corrosion resistance of the remanufactured magnet.

[0063] However, when it exceeds a certain range, nano-aluminum carbide will promote the formation of banded neodymium-rich phase and reduce the content of intergranular neodymium-rich phase, thereby weakening the demagnetizing coupling effect and reducing the coercive force of the remanufactured magnet. Nano-aluminum carbide is a non-magnetic phase, which reduces the remanufactured magnet's remanufactured magnetism and magnetic energy product. In addition, the neodymium-rich phase is unevenly distributed and its content increases, providing an atomic diffusion channel for the corrosion reaction of the neodymium-rich phase, and the corrosion resistance of the magnet deteriorates.

[0064] Embodiment 6-7

[0065] In Example 6-7, based on the preparation method of Example 1, the average particle size of the nano-aluminum carbide was adjusted. The adjustment details are shown in Table 3 below.

[0066] Comparative Examples 5-6

[0067] Comparative Examples 5-6 are based on the preparation method of Example 1, but the average particle size of the nano-aluminum carbide is adjusted. The adjustment details are shown in Table 3 below.

[0068] The remanufactured magnets obtained in Examples 6-7 and Comparative Examples 5-6 were subjected to the above performance tests, and the test results are shown in Table 3.

[0069] Table 3 Particle size table and performance test data table of nano-aluminum carbide of Example 1, Examples 6-7 and Comparative Examples 5-6

[0070]

[0071]

[0072] Referring to Table 3, by comparing Example 1, Examples 6-7 and Comparative Examples 5-6, it can be seen that as the particle size of nano-aluminum carbide continues to increase, the coercive force of the remanufactured magnet shows a trend of first increasing and then decreasing, and the remanent magnetism and the magnet energy product show a trend of first increasing and then tending to be stable. This may be because within a certain range, nano-aluminum carbide can optimize the microstructure of the magnet so that the intergranular neodymium-rich phase is gradually evenly distributed, and there is a good magnetic isolation effect between the main phase grains, thereby improving the coercive force of the remanufactured magnet, and the addition of nano-aluminum carbide will improve the orientation of the magnet, thereby improving the remanent magnetism and the magnet energy product of the remanufactured magnet until they tend to be stable.

[0073] However, beyond a certain range, nano-aluminum carbide will reduce the fluidity of the intergranular neodymium-rich phase, resulting in uneven distribution of the intergranular neodymium-rich phase between grains, reducing the demagnetizing coupling effect and the coercive force.

[0074] Embodiment 8-11

[0075] In Examples 8-11, based on the preparation method of Example 1, the weight ratio of the magnetic powder and nano-gallium nitride was adjusted. The adjustment details are shown in Table 4 below.

[0076] Comparative Examples 7-8

[0077] In Comparative Examples 7-8, based on the preparation method of Example 1, the weight ratio of the magnetic powder and nano-gallium nitride was adjusted. The adjustment details are shown in Table 4 below.

[0078] The remanufactured magnets obtained in Examples 8-11 and Comparative Examples 7-8 were subjected to the above performance tests, and the test results are shown in Table 5.

[0079] Table 4 Weight ratio of magnetic powder and nano-gallium nitride in Example 1, Examples 8-11 and Comparative Examples 7-8

[0080] Magnetic powder / g Nano-GaN / g Example 1 100 1 Example 8 100 0.4 Example 9 100 0.8 Example 10 100 1.2 Embodiment 11 100 1.5 Comparative Example 7 100 0.3 Comparative Example 8 100 1.6

[0081] Table 5 Performance test data of Example 1, Examples 8-11 and Comparative Examples 7-8

[0082]

[0083]

[0084] Referring to Table 5, by comparing Example 1, Examples 8-11 and Comparative Examples 7-8, it can be seen that as the content of nano-gallium nitride continues to increase, the magnetic properties of the remanufactured magnet show a trend of first increasing and then decreasing, and the corrosion resistance shows a trend of first increasing and then stabilizing. This may be because within a certain range, nano-gallium nitride improves the grain size and promotes the grain boundaries to become straight and complete, thereby improving the coercive force of the remanufactured magnet, and the addition of nano-gallium nitride will improve the orientation of the magnet, thereby improving the remanufactured magnet and the magnetic energy product of the magnet; and nano-gallium nitride gradually decomposes during sintering, increases the liquid phase ratio, and promotes the continuous doping of nano-34 into the grain boundaries as the liquid phase flows, thereby improving the magnetic properties of the remanufactured magnet; the nitrogen element produced by the decomposition of nano-gallium nitride combines with the oxygen element in the remanufactured magnet and is discharged, thereby improving the corrosion resistance of the remanufactured magnet.

[0085] However, beyond a certain range, the Ga atoms decomposed from nano-gallium nitride will continuously replace Fe atoms. The B-rich phase in the liquid phase is limited, and the replaced Fe atoms can only form Nd-Fe or other compounds, thereby destroying the Nd-Fe-B phase. More and more irregular phases are formed, and the grain size and distribution of the magnet become increasingly uneven, reducing the magnetic properties.

[0086] Examples 12-13

[0087] In Examples 12-13, based on the preparation method of Example 1, the average particle size of nano-gallium nitride was adjusted. The adjustment details are shown in Table 6 below.

[0088] Comparative Examples 9-10

[0089] Comparative Examples 9-10 are based on the preparation method of Example 1, but the average particle size of nano-gallium nitride is adjusted. The adjustment details are shown in Table 6 below.

[0090] The remanufactured magnets obtained in Examples 12-13 and Comparative Examples 9-10 were subjected to the above performance tests, and the test results are shown in Table 6.

[0091] Table 6 Particle size table and performance test data table of nano-gallium nitride of Example 1, Examples 12-13 and Comparative Examples 9-10

[0092]

[0093]

[0094] Referring to Table 6, by comparing Example 1, Examples 12-13 and Comparative Examples 9-10, it can be seen that as the particle size of nano-gallium nitride continues to decrease, the magnetic properties of the remanufactured magnet show a trend of first increasing and then tending to a stable state. This may be because nano-gallium nitride with smaller particle size is easier to decompose during high-temperature sintering, which promotes nano-aluminum carbide to enter the grain boundary, thereby improving the magnetic properties of the remanufactured magnet.

[0095] Examples 14-17

[0096] In Examples 14-17, based on the preparation method of Example 1, the sintering temperature and time were adjusted. The adjustment details are shown in Table 7 below.

[0097] Comparative Examples 11-12

[0098] Comparative Examples 11-12 are based on the preparation method of Example 1, but the sintering temperature and time are adjusted. The adjustment details are shown in Table 7 below.

[0099] The remanufactured magnets obtained in Examples 14-17 and Comparative Examples 11-12 were subjected to the above performance tests, and the test results are shown in Table 8.

[0100] Table 7 Data table of sintering temperature and sintering time of Example 1, Examples 14-17 and Comparative Examples 11-12

[0101] Sintering temperature / ℃ Sintering time / h Example 1 1120 5 Embodiment 14 1090 5 Embodiment 15 1090 6 Example 16 1100 6 Embodiment 17 1120 4 Comparative Example 11 1080 6 Comparative Example 12 1130 5

[0102] Table 8 Performance test data of Example 1, Examples 14-17 and Comparative Examples 11-12

[0103]

[0104]

[0105] Referring to Table 8, by comparing Example 1, Examples 14-17 and Comparative Examples 11-12, it can be seen that with the continuous increase of sintering temperature and sintering time, the magnetic properties and corrosion resistance of the remanufactured magnet show a trend of first increasing and then tending to be stable. This may be due to the continuous increase in sintering temperature, which promotes the continuous decomposition of nano-gallium nitride and the continuous entry of nano-aluminum carbide into the grain boundary with the liquid phase, thereby improving the magnetic properties and corrosion resistance of the remanufactured magnet until they tend to be stable.

[0106] Examples 18-21

[0107] Examples 18-21, based on Example 1, adjust the temperature and time of the first-stage tempering, and the specific adjustments are shown in Table 9.

[0108] Comparative Examples 13-14

[0109] Comparative Examples 13-14, based on Example 1, the temperature and time of the first-stage tempering were adjusted, and the specific adjustments are shown in Table 9.

[0110] The remanufactured magnets obtained in Examples 18-21 and Comparative Examples 13-14 were subjected to the above performance tests. The test results are shown in Table 10.

[0111] Table 9 Temperature and time of primary tempering of Example 1, Examples 18-21 and Comparative Examples 13-14

[0112] Temperature / ℃ Time / h Example 1 900 3 Embodiment 18 850 3 Embodiment 19 850 4 Embodiment 20 875 3 Embodiment 21 900 2 Comparative Example 13 830 4 Comparative Example 14 920 3

[0113] Table 10 Performance test results of Example 1, Examples 18-21 and Comparative Examples 13-14

[0114]

[0115]

[0116] Referring to Table 10, it can be seen from Example 1, Examples 18-21 and Comparative Examples 13-14 that as the primary tempering temperature continues to increase, the corresponding heating time continues to increase, and the magnetic properties and corrosion resistance of the remanufactured magnet continue to increase until they stabilize. This may be due to the fact that the first-stage heat treatment reduces the inhomogeneous phase in the main phase grains, thereby promoting the entry of nano-aluminum carbide into the intergranular phase, and also promoting the decomposed Ga atoms to replace Fe atoms, so that the magnetic properties and corrosion resistance of the remanufactured magnet continue to increase until they stabilize.

[0117] Examples 22-25

[0118] Examples 22-25, based on Example 1, adjust the temperature and time of the secondary tempering. See Table 11 for specific adjustments.

[0119] Comparative Examples 15-16

[0120] Comparative Examples 15-16, based on Example 1, the temperature and time of the first-stage tempering were adjusted, and the specific adjustments are shown in Table 11.

[0121] The remanufactured magnets obtained in Examples 22-25 and Comparative Examples 15-16 were subjected to the above performance tests. The test results are shown in Table 12.

[0122] Table 11 Temperature and time of secondary tempering of Example 1, Examples 22-25 and Comparative Examples 15-16

[0123] Temperature / ℃ Time / h Example 1 620 5 Embodiment 22 600 5 Embodiment 23 600 6 Embodiment 24 620 6 Embodiment 25 640 4 Comparative Example 15 580 6 Comparative Example 16 660 5

[0124] Table 12 Performance test results of Example 1, Examples 22-25 and Comparative Examples 15-16

[0125]

[0126]

[0127] Referring to Table 12, it can be seen from Example 1, Examples 22-25 and Comparative Examples 15-16 that as the secondary tempering increases, the corresponding heating time increases, and the magnetic properties and corrosion resistance of the remanufactured magnet show a trend of first increasing and then decreasing. It is possible that within a certain range, the secondary tempering temperature increases continuously to reduce the agglomeration of the rare earth-rich phase, thereby promoting the magnetic properties and corrosion resistance of the remanufactured magnet.

[0128] However, when the secondary tempering temperature exceeds a certain range, it will promote the growth of the main phase grains, causing the magnetic properties and corrosion resistance of the remanufactured magnet to gradually decrease.

[0129] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.

Claims

1. A method for preparing a remanufactured magnet using waste NdFeB magnets, characterized in that: The following steps are involved: (1) Preliminary crushing and analysis: The recycled waste NdFeB magnets are degreased, derusted and impurity-free, and then mechanically crushed to obtain a coarse waste powder, and then the content of each component in the coarse waste powder is analyzed; (2) preparing magnetic powder: hydrogen-crushing the waste coarse powder, and then jet milling the waste coarse powder to obtain magnetic powder; (3) Mixing: adding nano-gallium nitride and nano-aluminum carbide to the magnetic powder, mixing them evenly to obtain a mixed powder, and placing the mixed powder under nitrogen protection for compression molding to obtain a pressed embryo; (4) Sintering and tempering: the pressed green sheet is subjected to high temperature sintering, and then subjected to primary tempering and secondary tempering heat treatment to obtain a remanufactured magnet using waste NdFeB magnets; The mass ratio of the magnetic powder to the nano-aluminum carbide is 100: (0.25-1.5); The mass ratio of the magnetic powder to the nano-gallium nitride is 100:(0.25-1.5); The sintering temperature in step (4) is 1090-1120°C and the sintering time is 4-6h; In step (4), the green compact is kept at 850-900° C. for 2-4 hours for primary tempering, and then the green compact is cooled to a temperature less than 100° C. using argon gas. The green compact is then kept at 600-640° C. for 4-6 hours for secondary tempering, and then cooled to room temperature using argon.

2. The method for preparing a remanufactured magnet using waste NdFeB magnets according to claim 1, characterized in that: The average particle size of the nano-aluminum carbide is 30-50nm.

3. The method for preparing a remanufactured magnet using waste NdFeB magnets according to claim 1, characterized in that: The average particle size of the nano-gallium nitride is 10-30 nm.

4. A remanufactured magnet using waste NdFeB magnets prepared by the preparation method according to any one of claims 1 to 3.